2014
DOI: 10.1111/cea.12259
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐tryptase gene variation is associated with levels of circulating IgE and lung function in asthma

Abstract: summaryBackgroundTryptase, a major secretory product of human mast cells has been implicated as a key mediator of allergic inflammation. Genetic variation in the tryptases is extensive, and α-tryptase, an allelic variant of the more extensively studied β-tryptase, is absent in substantial numbers of the general population. The degree to which α-tryptase expression may be associated with asthma has not been studied. We have investigated the α-tryptase gene copy number variation and its potential associations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…Importantly, the portion of tryptase activity due to α/β-tryptase increases with the α-tryptase gene dosage. Consequently, an α-tryptase genedosage effect associated with a particular clinical phenotype, as shown in the current study for a cutaneous response to vibration or as reported for severe Dengue infection (Velasquez et al, 2015) or asthma (Abdelmotelb et al, 2014), might implicate involvement of α/β-tryptase. Also, as α-tryptase gene deficiency varies among individuals with Asian, European, and African backgrounds (Trivedi et al, 2009), affecting α/β-tryptase content, a role for these heterotetramers can now be considered in the context of natural selection.…”
Section: Discussionsupporting
confidence: 55%
“…Importantly, the portion of tryptase activity due to α/β-tryptase increases with the α-tryptase gene dosage. Consequently, an α-tryptase genedosage effect associated with a particular clinical phenotype, as shown in the current study for a cutaneous response to vibration or as reported for severe Dengue infection (Velasquez et al, 2015) or asthma (Abdelmotelb et al, 2014), might implicate involvement of α/β-tryptase. Also, as α-tryptase gene deficiency varies among individuals with Asian, European, and African backgrounds (Trivedi et al, 2009), affecting α/β-tryptase content, a role for these heterotetramers can now be considered in the context of natural selection.…”
Section: Discussionsupporting
confidence: 55%
“…29–31 There is also some evidence that polymorphisms or copy number variations in other mast cell–derived proteases, including α-tryptase and chymase, are correlated with the serum IgE level. 3234 However, in vivo human IgE has been postulated to associate with other plasma proteins, including α 1 -antitrypsin, to protect it from degradation. 30 …”
Section: Explanations For the Short Serum Half-life Of Igementioning
confidence: 99%
“…Individuals with 4 active β genes lack α genes altogether, a situation that arises because α genes in most cases are alleles at a locus that also accepts β genes. Some individuals also may have duplicated loci containing α genes (Abdelmotelb et al, 2014). Among active β tryptases, one of the common variations is loss of an N-linked glycosylation site in βII tryptase, compared to the classical βI form, which may alter stability.…”
Section: Tryptasesmentioning
confidence: 99%